Adoptive immunotherapy with double‐bright (CD56bright/CD16bright) expanded natural killer cells in patients with relapsed or refractory acute myeloid leukaemia: a proof‐of‐concept study. (7th September 2021) - Silla, Lucia; Valim, Vanessa; Pezzi, Annelise; da Silva, Maria; Wilke, Ianae; Nobrega, Juliana; Vargas, Alini; Amorin, Bruna; Correa, Bruna; Zambonato, Bruna; Scherer, Fernanda; Merzoni, Joice; et al.
Summary: Patients with acute myeloid leukaemia (AML) have a five‐year survival rate of 28·7%. Natural killer (NK)‐cell have anti‐leukaemic activity. Here, we report on a series of 13 patients with high‐risk R/R AML, treated with repeated infusions of double‐bright (CD56 bright /CD16 bright ) expanded NK cells at an academic centre in Brazil. NK cells from HLA‐haploidentical donors were expanded using K562 feeder cells, modified to express membrane‐bound interleukin‐21. Patients received FLAG, after which cryopreserved NK cells were thawed and infused thrice weekly for six infusions in three dose cohorts (10 6 –10 7 cells/kg/infusion). Primary objectives were safety and feasibility. Secondary endpoints included overall response (OR) and complete response (CR) rates at 28–30 days after the first infusion. Patients received a median of five prior lines of therapy, seven with intermediate or adverse cytogenetics, three with concurrent central nervous system (CNS) leukaemia, and one with concurrent CNS mycetoma. No dose‐limiting toxicities, infusion‐related fever, or cytokine release syndrome were observed. An OR of 78·6% and CR of 50·0% were observed, including responses in three patients with CNS disease and clearance of a CNS mycetoma. Multiple infusions of expanded, cryopreserved NK cells were safely administered after intensive chemotherapy in high‐risk patients with R/R AML and demonstrated encouraging outcomes.